Investigations on the anti-diabetic potential of novel marine seaweed Sargassum longiotom against alloxan-induced diabetes mellitus: A pilot study (Bangladesh Journal of Pharmacology, 2014)
The present study evaluated the hypoglycemic effect of brown algae Sargassum longiotom in alloxan-induced diabetic rats. After the treatment with S. longiotom extract, there is a significant reduction (p